고등학생 청소년들의 수면과 자살위험요인 - 정자현(Ja-Hyun Jeong), 장용이(Yong-E Jang), 이해우(Hae-Woo Lee), 심현보(Hyun-Bo Shim), 최진숙(Jin-Sook Choi) (Sumyŏn--chŏngsin saengni, 2013)
Objectives: Sleep problems has been consistently reported as a suicidal risk factor in adults and, recently, also in adolescents. In this study, dividing study subjects by the previous suicidal behaviors (suicidal vs non-suicidal), we compared the group differences of suicidal risk factors, and examined the possibility of sleep as a suicidal risk factor. Methods: Study subjects were 561 (271 boys and 290 girls) from a community sample of high school students. Suicidal Risk Behavior Checklist, Center for Epidemiological Study-Depression (CES-D), Symptom Checklist-90-Revision (SCL-90-R) Anxiety and Aggression subscale, Pittsburg Sleep Quality Index (PSQI) were done. Results: Forty six students (8.1%) reported previous actual self-harm behavior as a suicidal attempt, 181 students (32.4%) reported having suicidal thought only. Three hundred thirty four students (59.5%) reported no previous suicidal behavior (thought and attempt, both). Suicidal behavior group showed higher score on risk behaviors such as school violence, substance use and internet addiction. CES-D, SCL-90-R, PSQI showed significant group difference. Logistic regression analysis showed suicidal risk were significantly associated with depression, stress in suicidal risk factors and sleep latency, daytime dysfunction in PSQI. Analysis of variance (ANOVA) shows the most prolonged sleep latency and increased index of all PSQI components except sleep efficiency in suicidal attempt group. Conclusions: Sleep Problems had a strong association with the suicidal risk behavior in adolescents. Sleep problems, especially, prolonged sleep latency, daytime dysfunction might be important markers for suicidal behavior. Screening for sleep problems in adolescents are encouraged for the parents, school teachers, and related medical physicians. 목 적: 수면 문제는 지속적으로 성인의 자살 위험 요인으로 보고되어왔고 최근에는 청소년을 대상으로도 그 가능성이 보고되고 있다. 본 연구는 과거의 자살 행동 유무에 따라 대상군을 분류하여 이들 사이의 자살위험요인과 수면양상을 비교하고 자살위험요인으로써의 수면의 가능성을 평가해 보았다. 방 법: 고등학생 561명(남 271명, 여 290명)을 대상으로 자살위험행동 체크리스트, Center for Epidemiological Study-Depression(CES-D), Symptom Checklist-90-Revision(SCL-90-R) 불안, 공격성 하위척도, Pittsburg Sleep Quality Index(PSQI)가 시행되었다. 결 과: 46명(8.1%)이 자살시도 목적으로 자기 위해 행동을 한 경험이 있었고, 181명(32.4%)은 자살사고 경험만을 보고했다. 334명(59.5%)은 과거 자살위험행동(사고, 시도)을 보이지 않았다. 자살 위험군은 학교 폭력, 물질남용, 인터넷 중독, CES-D, SCL-90-R, PSQI에서 비자살 위험군에 비해 유의하게 점수가 높았다. 로지스틱 회귀분석의 결과 자살위험행동은 우울, 스트레스와 상관성을 보였고, PSQI에서는 수면 잠복기, 주간기능장애에서 상관성을 보였다. 일원분산분석(ANOVA, Analysis of variance)에서는 자살 시도군에서 수면 잠복기의 연장, PSQI 지수의 증가가 가장 심하게 관찰되었다. 결 론: 수면문제는 청소년군의 자살위험행동과 높은 연관성을 보인다. 특히 수면 잠복기, 주간기능장애가 자살위험행동의 중요한 인자일 것으로 여겨진다. 추후 부모, 교사, 의료인들에 의한 청소년의 수면에 대한 지속적인 평가와 관리를 권장하는 바이다.